Cause and effect of construction delay (Bumiputera Company) / Muhammad Faiz Mohd Tarjuddin - Mohd Tarjuddin, Muhammad Faiz (Faculty of Architecture , Planning and Surveying, 2015)
Completion of construction project on time is an important key of successful. Late completion of works on time is defined as delay. Nowadays,delays are one of the huge problems facing by the construction industry. The delay in construction project gives many consequences and also gives impact to the involved parties.The three main objectives of this study are to examine the causes of delay on the construction projects, to recognize the effects and consequences of construction delays and to recommend the ways to reduce construction delays in development.A complete literature was conducted to build up general understanding and knowledge to identify this causes and effects. A questionnaire survey and interview was conducted in order to identify these issues involving the respondents from clients, contractors and consultants. About 48 respondents participated in the survey.The data analysis from the survey then has been ranked based on their mean. There are thirty one delay causes in the questionnaire survey that has been identified. The causes have been grouped in 9 categories which were project, client, contractor, consultant, design, material,equipment, labour and external factors. The proposed methods also have been recognized in order to solve and minimize the delay problem in construction industry.